Biomechanical framework for the inverse dynamic analysis of swimming using hydrodynamic forces from swumsuit - Sequeira, M.; Simões, F.; Quental, C.; Ambrósio, J; Fonseca, P.; Vilas-Boas, J. P.; Nakashima, M. (Computer Methods in Biomechanics and Biomedical Engineering, 2023)
This study aims to integrate an open-source software capable of estimating hydrodynamic forces solely from kinematic data with a full-body biomechanical model of the human body to enable inverse dynamic analyses of swimmers. To demonstrate the methodology, intersegmental forces and joint torques of the lower limbs were computed for a six-beat front crawl swimming motion, acquired at LABIOMEP-UP. The hydrodynamic forces obtained compare well with existing numerical literature. The intersegmental forces and joint torques obtained increase from distal to proximal joints. Overall, the results are consistent with the limited literature on swimming biomechanics, which provides confidence in the presented methodology.